2019
DOI: 10.1136/bmjopen-2019-030068
|View full text |Cite
|
Sign up to set email alerts
|

The Only Eye Study (OnES): a qualitative study of surgeon experiences of only eye surgery and recommendations for patient safety

Abstract: ObjectivePerforming surgery on patients with only one seeing-eye, where complications may result in catastrophic vision loss, presents unique challenges for the ophthalmic care team. There is currently no evidence regarding how surgeons augment their care when treating only eye patients and no guidelines for how these patients should be managed in hospital eye services. This study aimed to explore ophthalmic surgeons’ experiences of only eye surgery and perceptions of current practice.Design and participantsTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Multiple studies have shown that intensive VF monitoring could help to identify and prioritize individuals most at risk of debilitating sight loss 11 , 12 , 13 , 14 , 15 (i.e., younger patients with fast-progressing VF loss 16 ). Frequent (e.g., monthly) monitoring is likely to be of particular benefit for those patients for whom rapid progression is most likely (e.g., optic disk hemorrhage 17 , 18 , 19 ) or most costly (e.g., monocular vision 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that intensive VF monitoring could help to identify and prioritize individuals most at risk of debilitating sight loss 11 , 12 , 13 , 14 , 15 (i.e., younger patients with fast-progressing VF loss 16 ). Frequent (e.g., monthly) monitoring is likely to be of particular benefit for those patients for whom rapid progression is most likely (e.g., optic disk hemorrhage 17 , 18 , 19 ) or most costly (e.g., monocular vision 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first research output (OnES 1) identified recommendations on how to optimise patient safety from surgeons' perspectives, and the role of purpose-designed training fellowships and Open access stress-reducing strategies in high-stakes procedures. 12 In this study, we make recommendations for surgical care explored through the patient perspective. Based on our interview findings, we developed a model for optimal patient-centred care in only eye surgery (see online supplemental appendix 1).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who met our criteria for being an only eye patient were invited to participate in a semistructured interview. As described in our previous work, 12 the definition of an only eye was where significant loss of vision in this eye would be deemed life changing with profound impact on a patient’s quality of life. VA in the fellow eye of <3/60 or worse ± end-stage visual field loss was considered insufficient to maintain the patient’s current independent lifestyle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations